Duration of FOLFOX Adjuvant Chemotherapy in High-Risk Stage II and Stage III Colon Cancer With Deficient Mismatch Repair - Hu, Huabin; Wu, Zehua; Wang, Chao; Huang, Yan; Zhang, Jianwei; Cai, Yue; Xie, Xiaoyu; Li, Jianxia; Shen, Cailu; Li, Weiwei; Ling, Jiayu; Xu, Xuehu; et al. (Frontiers in Oncology, 2020)
Background We evaluated the impact of 3 months of mFOLFOX6 adjuvant chemotherapy or surgery alone in comparison with 6 months of mFOLFOX6 on disease-free survival (DFS) in deficient mismatch repair (dMMR) colon cancer (CC) patients. Methods This retrospective study identified a cohort of patients with high-risk stage II and III dMMR CC who underwent curative surgery between May 2011 and July 2019. DFS was compared using the Kaplan-Meier survival methods and Cox proportional hazards models. Propensity-score matching was performed to reduce imbalance in baseline characteristics. Results A total of 242 dMMR CC patients were identified; 66 patients received 6 months of mFOLFOX6, 87 patients received 3 months of mFOLFOX6, and 89 patients were treated with surgery alone. The 3-year DFS rate was 72.8% in 3-month therapy group and 86.1% in 6-month therapy group, with a hazard ratio (HR) of 2.78 (95CI%, 1.18 to 6.47; P= 0.019). The difference in DFS between surgery alone group and 6-month therapy group was also observed but was nonsignificant (HR= 2.30, 95%CI, 0.99 to 5.38; P=0.054). The benefit of 6-month therapy in DFS compared with 3-month therapy group was pronounced for patients with stage III (HR=2.81, 95%CI, 1.03 to 7.67; P=0.044) but not for high-risk stage II patients. Propensity score matched analysis confirmed a DFS benefit in the 6-month therapy group. Conclusion This study suggested that a 6-month duration of mFOLFOX6 adjuvant chemotherapy in dMMR CC patients may be associated with improved DFS compared with 3-month therapy, particularly in patients with stage III. The observational nature of the study implies caution should be taken in the interpretation of these results.